The Role of Pashto (as L1) and Urdu (as L2) in English Language Learning - Ayesha Saddiqa (Linguistics and Literature Review, 2018)
Pashto is one of the dominant languages in the north of Pakistan. Its speakers prefer to communicate in L1with their peers in non-pashto speaking regions like Lahore, which is the capital city of Punjab, Pakistan. Along with Pashto, they communicate in Urdu (the national language) and English (the most prestigious academic language) for higher education, employment and business. With this background in mind, the current study investigates: (a) what are the common syntactic properties (sentence structure, aspect, preposition, article and mood) in Pashto, Urdu and English languages?, (b) What are the advantages and/ or disadvantages to Pashto speakers in English language learning? and (c) What is the potential role of Urdu in English language learning? Linguistic Proximity Model was used as a theoretical framework to analyze the data. The data was gathered from 19 Bachelor of Science Pashto students of different programs from three universities located in Lahore. The participants were asked to translate sentences from Urdu to English and from Pashto to English to find interference of both Pashto and Urdu in learning the English language. Unlike many studies, the present study negates the facilitative role of background languages in learning the target language. Apparently, although Urdu serves as a base for learning the English language, the present study recommends an independent investigation to explore the role of the Urdu language in learning English.